Modelling social mobilisation – an interdisciplinary exploration of twitter as a mediating tool for social acts and information networks. (2013) - Amor, J.D.; Foss, J.; Gkotsis, G.; Grainger-Clemson, H.; Marchis, E.; Azhar, F.
No abstract available